2014
DOI: 10.1002/phar.1501
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in Continuous-Flow Left Ventricular Assist Devices: Pathophysiology, Prevention, and Pharmacologic Management

Abstract: Continuous-flow left ventricular assist devices reduce short-term mortality and improve quality of life in patients with end-stage heart failure. Unfortunately, device-related complications remain common, with many patients experiencing adverse events within the first year. New literature suggests that rates of device-related thrombosis may be increasing since 2011, which is particularly troublesome given that this pathology can result in a disabling stroke, organ damage, and death. In 2013, a group of practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…Currently, ASA is the dominant and often sole agent utilized, at doses of 81 – 325 mg/day, for patients implanted with continuous flow VADs, which are comparable to those we have emulated in the present study [50]. Despite ASA management, VAD thrombosis continues to occur to varying degrees in patients and recently has been on the rise [4].…”
Section: Discussionsupporting
confidence: 67%
“…Currently, ASA is the dominant and often sole agent utilized, at doses of 81 – 325 mg/day, for patients implanted with continuous flow VADs, which are comparable to those we have emulated in the present study [50]. Despite ASA management, VAD thrombosis continues to occur to varying degrees in patients and recently has been on the rise [4].…”
Section: Discussionsupporting
confidence: 67%
“…Thrombolysis has been attempted in HVAD thrombosis with adequate success rates, but major hemorrhage occurred in Ďł1/3 of patients. 49 Similar rates of thrombus resolution have been reported using direct thrombin inhibitor treatment as with thrombolysis. Eptifibatide resolved thrombosis in only one-quarter of cases and major bleeding rates are unacceptably high with eptifibatide treatment.…”
Section: Thrombosis Of Continuous Flow Vads In Adolescents and Adultssupporting
confidence: 52%
“…Experts in hemostasis can significantly impact care of patients requiring MCS and are a necessary part of the management team. 51 9/10 (90) 1/10 (10) † Eptifibatide 49 7/27 (26) 13/27 (48) *Includes intraventricular and systemic fibrinolytics. †Minor hemorrhage only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower rotation speed is sometimes indicated to reduce the grade of AI, 14,30) but it may be associated with a higher risk of pump thrombosis, lower exercise tolerability, 31) or inadequate stimulation of sympathetic activity. 32,33) Some authors reported successful trans-catheter aortic valve replacement during LVAD support, but the procedure has a risk of migration of the replaced device owing to the strong vacuum of blood into apical VAD inflow.…”
mentioning
confidence: 99%